5 (Lima) UU RI No.16, 17, 18, 19, 20 Th.2000 ttg perubahan kedua atas UU No.6... - [Tidak Terdaftar] (Cipta Jaya, 2000)
5 (Lima) UU RI No.16, 17, 18, 19, 20 Th.2000 ttg perubahan kedua atas UU No.6 th 1983...